Postharvest technology of fruit and vegetables - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Postharvest technology of fruit and vegetables by A Keith Thompson 1996 4 16pp price UKL70 00 ISBN 0 632 04037 8